OP26 The first real-life multicentre prospective validation study of the electronic chromoendoscopy score (Paddington International Virtual ChromoendoScopy ScOre) and its outcome in ulcerative colitis. (15th January 2020) - Iacucci, M; Smith, S C; Bazarova, A; Shivaji, U N; Bhandari, P; Cannatelli, R; Daperno, M; Ferraz, J G; Goetz, M; Gui, X; Hayee, B; De Hertogh, G; et al.
Abstract: Background: Mucosal healing is an important goal in the treatment of ulcerative colitis (UC). The newly published PICaSSO score characterises subtle mucosal and vascular changes and defines mucosal healing. We aimed to validate in real-life the PICaSSO score and assess its ability to predict relapse. Methods: Patients with UC were prospectively recruited from 11 international centres. Participating endoscopists experienced in IBD received training on PICaSSO before starting the study. The rectum and sigmoid were examined using iScan 1, 2 and 3 (Pentax, Japan) and inflammatory activity was assessed using UCEIS and PICaSSO. Biopsies were taken for the histological assessment using Robarts Histological Index (RHI) and Nancy. Follow-up was obtained at 12 months. Results: A total of 278 patients were recruited (Table 1). The diagnostic performance in predicting histologic healing is shown in Table 2. When using PICaSSO score of ≤3 for mucosal and vascular architecture the AUROC to predict healing by RHI is 0.79 (95% CI 0.74–0.85) and 0.73 (95% CI 0.68–0.80) respectively and when using the Nancy score the AUROC is 0.78 (95% CI 0.72–0.84) and 0.77 (0.71–0.84). A total PICaSSO score of ≤8 and UCEIS score of ≤1 predicts remission at 12 months with an AUROC of 0.73 (0.65–0.80) and 0.71 (0.64–0.79). A Kaplan–Meier curve shows a favourable survival probability without relapse with a PICASSO score of ≤8 (Figure 1). Conclusion: This real-life validation study shows the PICaSSO score can predict accurately histological healing and long-term remission and can be a useful tool in the management of UC.